Structural Equation Modelling in the Research of Entrepreneurial Orientation: A Systematic Literature Review - Hrubý, Vojtěch (Univerzita Tomase Bati ve Zline, 2021)
Objective: To systematically review recent research of the entrerpreneurial orientation utilising structural equation models. In particular, to review trends in number of research papers on these subjects, assess the methods used, number and type of the entrepreneurial orientation's dimensions and measures used. Method: Web of Science database was first searched separately for the terms 'entrepreneurial orientation' and 'structural equation modelling' between 2011 and 2020 to look for trends in number of articles, countries where the research had been conducted and categores it was assigned to. In the second phase the Web of Science was serched for the combinateion of the two terms between 2019 and 2020 in title, abstract, key words, adn key words plus. Exclusion and inclusion criteria were applied and data from selected articles was extracted using an extraction form and statistically analysed. Results: The number of articles on both the entrepreneurial orientation and the structural equation modelling has been growing and the growth has accelerated in the last three years. 20 (39%) articles were selected out of 51 hits resulting from the combined search. Research had taken place in 14 countries of which 5 amounted to 55% of all studies. 89% of studies were clasified in at least one of the three Web of Science categories: business, management, economics. Average sample size was 278 companies and the most frequently used method was PLS-SEM. 85% articles propoesed recommendations for future research. The entrepreneurial orientation had mostly been measured with (Covin and Slevin, 1989) measure (46%) and 3 dimensions had been used in 90% of studies. Conclusions: the theoretical concept of Entrepreneurial Orientation has been gaining popularity and structural equation modelling has been frequently used to analyse various correlations. PLS-SEM is the most frequetnly used method as well as the selection of 3 dimensions measured by the original (Covin and Slevin, 1989) measure.

Objective: To systematically review recent research of the entrerpreneurial orientation utilising structural equation models. In particular, to review trends in number of research papers on these subjects, assess the methods used, number and type of the entrepreneurial orientation's dimensions and measures used. Method: Web of Science database was first searched separately for the terms 'entrepreneurial orientation' and 'structural equation modelling' between 2011 and 2020 to look for trends in number of articles, countries where the research had been conducted and categores it was assigned to. In the second phase the Web of Science was serched for the combinateion of the two terms between 2019 and 2020 in title, abstract, key words, adn key words plus. Exclusion and inclusion criteria were applied and data from selected articles was extracted using an extraction form and statistically analysed. Results: The number of articles on both the entrepreneurial orientation and the structural equation modelling has been growing and the growth has accelerated in the last three years. 20 (39%) articles were selected out of 51 hits resulting from the combined search. Research had taken place in 14 countries of which 5 amounted to 55% of all studies. 89% of studies were clasified in at least one of the three Web of Science categories: business, management, economics. Average sample size was 278 companies and the most frequently used method was PLS-SEM. 85% articles propoesed recommendations for future research. The entrepreneurial orientation had mostly been measured with (Covin and Slevin, 1989) measure (46%) and 3 dimensions had been used in 90% of studies. Conclusions: the theoretical concept of Entrepreneurial Orientation has been gaining popularity and structural equation modelling has been frequently used to analyse various correlations. PLS-SEM is the most frequetnly used method as well as the selection of 3 dimensions measured by the original (Covin and Slevin, 1989) measure.
Structural Equation Modelling in the Research of Entrepreneurial Orientation: A Systematic Literature Review
Keywords: Autonomy; Competitive Aggressiveness; Innovativeness; Partial Least Square; Proactiveness; Risk-taking; Autonomy; Competitive Aggressiveness; Innovativeness; Partial Least Square; Proactiveness; Risk-taking